PENGARUH PERTUMBUHAN PENJUALAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Wahyuni, Wahyuni; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2023)
The Effect of Sales Growth and Leverage on Company Value in Mining Companies Listed on the Indonesian Stock Exchange with Financial Performance as an Intervening Variable. The purpose of this study is to determine the effect of sales growth and leverage on company value in mining companies listed on the Indonesian stock exchange with financial performance as an intervening variable. The population in this study was all mining companies, totaling 57 companies. The sampling technique in this study used purposive sampling so that 6 samples were obtained. The results of the direct and indirect hypothesis test using the Smart PLS 3.0 application, the direct effect hypothesis test shows that sales growth has a positive but not significant effect on financial performance, leverage has a significant negative effect on financial performance, sales growth has a significant positive effect on company value, leverage has a significant effect positive but not significant to company value, and financial performance has a significant positive effect on company value. The results of the indirect effect test show that sales growth has a positive but not significant effect on company value through financial performance, leverage has a significant negative effect on company value through financial performance.